2015
DOI: 10.1021/acs.orglett.5b01211
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembly of [3]Catenanes and a [4]Molecular Necklace Based on a Cryptand/Paraquat Recognition Motif

Abstract: Hierarchical self-assembly centered on metallacyclic scaffolds greatly facilitates the construction of mechanically interlocked structures. The formation of two [3]catenanes and one [4]molecular necklace is presented by utilizing the orthogonality of coordination-driven self-assembly and crown ether-based cryptand/paraquat derivative complexation. The threaded [3]catenanes and [4]molecular necklace were fabricated by using ten and nine total molecular components, respectively, from four and three unique specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(16 citation statements)
references
References 65 publications
0
13
0
Order By: Relevance
“…A more recent synthesis of radial [ n ]­catenanes similarly dimerizes the ends of pseudo[2]­rotaxanes, i.e., a ring-threaded linear axle that is capped with bulky end groups to discourage dethreading. The dimerization of such pseudo[2]­rotaxanes into cycles creates “molecular necklaces”, as the linkage between pseudorotaxanes serves as a bulky knot beyond which the rings cannot easily pass, similar to the knots between pearls or beads on such a necklace. Thus, the minor rings localized on a molecular necklace do not translate freely on the major ring. This is in contrast to Sauvages’s metal-templated catenanes, where removal of the templating metal allows the minor rings to translate completely around the major ring, which is an important assumption of our model.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A more recent synthesis of radial [ n ]­catenanes similarly dimerizes the ends of pseudo[2]­rotaxanes, i.e., a ring-threaded linear axle that is capped with bulky end groups to discourage dethreading. The dimerization of such pseudo[2]­rotaxanes into cycles creates “molecular necklaces”, as the linkage between pseudorotaxanes serves as a bulky knot beyond which the rings cannot easily pass, similar to the knots between pearls or beads on such a necklace. Thus, the minor rings localized on a molecular necklace do not translate freely on the major ring. This is in contrast to Sauvages’s metal-templated catenanes, where removal of the templating metal allows the minor rings to translate completely around the major ring, which is an important assumption of our model.…”
Section: Resultsmentioning
confidence: 99%
“…A radial [ n +1]­catenane is a molecule of one main ring onto which n minor rings are interlocked . There exist a handful of reported syntheses of radial [ n +1]­catenanes, starting with Sauvage’s classic synthesis of multicatenanes of n ≤ 6, followed later by many other syntheses, among them “molecular necklaces” Our focus is on the mechanical conformers of radial [ n +1]­catenanes where the minor rings have some asymmetry, as for example, a pendant or a charged group. A simple way to model this asymmetry in the minor ring is invoke a force center located a fixed distance from the minor ring center; we represent this as a force center at the end of a rod, directed outward from the major ring, as represented in Figure .…”
Section: Introductionmentioning
confidence: 99%
“…Paraquat ( N,N ′‐dialkyl‐4,4′‐bipyridinium) derivatives, such as g1 [2a] and g2 ,[2b] have been widely used as guests for crown ether hosts, forming pseudorotaxanes, which can in turn be used to fabricate advanced supramolecular species, such as rotaxanes, catenanes, polypseudorotaxanes, polyrotaxanes, and polycatenanes. [3, 4] It was found that bis( meta‐ phenylene)‐32‐crown‐10 (BMP32C10) derivatives ( 1 ) with paraquats tend to form “taco” structures in the solid state, instead of pseudorotaxane complexes (Scheme ). [5] The “taco” structure is considered a contributing conformation in solution, but the pesudorotaxane structure coexists, as confirmed by the formation of rotaxanes and catenanes from such solutions.…”
Section: Introductionmentioning
confidence: 99%
“…Interlocked compounds composed of three or more components recently attracted great interest due to the remarkable progress in the synthesis of these complex compounds. Some examples of the interlocked compounds with three components are depicted in Figure . A [3]­rotaxane (type 1.2) is composed of two ring components and one axle component .…”
Section: Introductionmentioning
confidence: 99%